The WOW Project: An Experiential Learning Approach to Developing Teamwork and Project Management Competencies in South African Engineering Education - Lourens, Ann; Mapaling, Curwyn; Truter, Nicole (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This paper examines the implementation and impact of a Workplace Orientation Workshop within a South African industrial engineering programme, designed to cultivate essential graduate attributes mandated by the Engineering Council of South Africa. The study was guided by three research questions: how the WOW Project aligned with ECSA’s GA8 criteria, how student participation contributed to teamwork and project management competencies, and what insights student reflections offered about the role of experiential learning in shaping responsible engineering practice. Employing a qualitative methodology, the study analyses student reflections on their participation in the Workplace Orientation Workshop Project. The analysis revealed three prominent themes: (i) preparation for professional transition; (ii) project management and leadership experience; and (iii) enhanced communication and interpersonal skills. Grounded in situated learning theory and problem-based learning principles, the WOW Project provided a practical platform for students to apply engineering management principles and develop critical competencies through experiential learning. Findings highlight the effectiveness of the WOW Project in bridging the gap between academic learning and professional readiness, fostering responsible engineering practices. Recommendations include expanding the scope of future Workplace Orientation Workshop Events and implementing structured feedback mechanisms to enhance student learning outcomes.